2016
DOI: 10.1016/j.fsi.2016.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis by iTRAQ in red claw crayfish, Cherax quadricarinatus, hematopoietic tissue cells post white spot syndrome virus infection

Abstract: To elucidate proteomic changes of Hpt cells from red claw crayfish, Cherax quadricarinatus, we have carried out isobaric tags for relative and absolute quantitation (iTRAQ) of cellular proteins at both early (1 hpi) and late stage (12 hpi) post white spot syndrome virus (WSSV) infection. Protein database search revealed 594 protein hits by Mascot, in which 17 and 30 proteins were present as differentially expressed proteins at early and late viral infection, respectively. Generally, these differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The hemocytes are the main site in crustaceans where the immune defense is mounted. Proteomics have been widely used to investigate the molecular mechanisms underlying the immune response to WSSV infection in crustaceans but there is no research available on V. alginolyticus infection yet ( 11 , 12 ). Currently an isobaric tag-based methodology for peptide relative quantification [isobaric tags for relative and absolute quantitation (iTRAQ)] coupled to multidimensional liquid chromatography and tandem mass spectrometry enables the assessment of protein levels where four samples can be compared for their common effects ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hemocytes are the main site in crustaceans where the immune defense is mounted. Proteomics have been widely used to investigate the molecular mechanisms underlying the immune response to WSSV infection in crustaceans but there is no research available on V. alginolyticus infection yet ( 11 , 12 ). Currently an isobaric tag-based methodology for peptide relative quantification [isobaric tags for relative and absolute quantitation (iTRAQ)] coupled to multidimensional liquid chromatography and tandem mass spectrometry enables the assessment of protein levels where four samples can be compared for their common effects ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The digested peptides were labeled using iTRAQ reagents (iTRAQ ® Reagents-8plex kit, Sigma Chemical Co., St. Louis, MO, USA) [ 65 , 66 , 67 ]. The labeled samples were pooled and purified using SCX chromatography on an Agilent 1260 HPLC (Agilent Technologies Inc., Santa Clara, CA, USA) [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main viral pathogens that cause diseases in crustaceans include WSSV, 31,32 yellow-head virus, 33 hepatopancreatic parvo-like virus, 34,35 infectious hypodermal and haematopoietic necrosis virus (IHHNV) 36,37 and monodon baculovirus. [38][39][40] Besides the pathological effects of these viruses, studies using genomics, [41][42][43] transcriptomics 44,45 and proteomics [46][47][48] vate and lactic acid) were found. 52 Similarly, elevated levels of some key metabolites of glycolysis (glucose), nucleotide metabolism (uracil and inosine), amino acid biosynthesis (alanine, tryptophan, histidine, tyrosine, methionine, valine, leucine and isoleucine), TCA cycle (fumaric acid) and lipid metabolism have been found in gills of WSSVinfected crayfish Cherax quadricarinatus.…”
Section: Viral-induced Metabolic Changes In Crustaceansmentioning
confidence: 99%
“…The main viral pathogens that cause diseases in crustaceans include WSSV, 31,32 yellow‐head virus, 33 hepatopancreatic parvo‐like virus, 34,35 infectious hypodermal and haematopoietic necrosis virus (IHHNV) 36,37 and monodon baculovirus 38–40 . Besides the pathological effects of these viruses, studies using genomics, 41–43 transcriptomics 44,45 and proteomics 46–48 have revealed that viral infections cause metabolic changes in crustaceans. For instance, the voltage‐dependent anion channel (VDAC), which controls the influx and efflux of metabolites and ions through the mitochondrial membrane to drive cell energy metabolism, plays a pivotal role in WSSV infection in various crustaceans such as penaeid shrimp P .…”
Section: Changes In Host Metabolomementioning
confidence: 99%